INDUSTRIALISASI PEMBANGUNAN RUMAH SUSUN: PARADIGMA INDUSTRI KONSTRUKSI DI INDONESIA - Agusinta Dewi, Ni Ketut (Jurnal Natah; Vol. 3, No. 1 Februari 2005, 2012)
In this moment, the method of housing development were already friction between conventional method and industry method. Paradigm of housing development in developing countries, include Indonesia, make use of industrialization as development.strategy. This case needs the transfer technology from industry countries to developing countries. The paper discusses the friction of housing development method and the transfer technology in construction industry of Indonesia.
Keywords: industry, industrialization, construction industry, flat